Becoming a Good Farmer—Becoming a Good Farm Worker: On Colonial Educational Policies in Germany and German South-West Africa, Circa 1890 to 1918 - Jakob Zollmann (Education and Development in Colonial and Postcolonial Africa. Policies, Paradigms, and Entanglements, 1890s–1980s, 2020)
This chapter analyzes the training provided to Germans who were eager to become farmers in German South-West Africa (GSWA) and considers related debates on the uses of colonial knowledge and tropical agriculture for the profit of the colony. The chapter considers (1) how colonial enthusiasts and administrators viewed the need for an improved tropical agricultural education given the setbacks encountered in GSWA; (2) how knowledge related to tropical agriculture was institutionalized and administered; (3) how, in Germany, two schools for tropical agriculture were set up; and (4) how the debate about an “education to work” for the African workforce in GSWA resulted in the willful exclusion of this group from the most elementary forms of education.
Keywords: 300